The commercial varieties of winter durum wheat varieties and the features of their seed-growing - N. E. Samofalova; N. P. Ilichkina; M. A. Avramenko; O. A. Dubinina; T. G. Derova (Зерновое хозяйство России, 2018)
The article presents the information about significance and spread of durum wheat, the reasons of deficit of durum grain in the country and the ways to improve production of this valuable crop. One of the ways is to introduce the commercial varieties of winter durum wheat ‘Amazonka’, ‘Agat donskoy’, ‘Kristella’, ‘Lazurit’ and ‘Oniks’, listed in the State Register of breeding achievements in North-Caucasus and Nizhniy-Volga region from 2010 till 2015. The new varieties possess high genetic potential of productivity. The average productivity during the years of trials (2011-2015) was 6.81 t/ha (the variety ‘Kristella’), 7.37 t/ha (the variety ‘Lazurit’); in the favourable year of 2014 they produced 8.24 and 8.80 t/ha respectively and in the unfavourable year of 2012 they gave 4.96 and 6.0 t/ha. The varieties ‘Amazonka’, ‘Agat donskoy’ and ‘Lazurit’ have got a high degree of frost resistance; the varieties ‘Kristella’ and ‘Oniks’ have got the average degree, giving way to ‘Donchanka’ on 8-18% with high drought tolerance especially in the period of ripening. The variety ‘Kristella’ belongs to the middle early maturing group, the varieties ‘Amazonka’, ‘Oniks’ and ‘Diona’ belong to middle maturing group and the varieties ‘Agat donskoy’ and ‘Lazurit’ belong to middle later maturing group. The varieties of short stem type are resistant to lodging (4-5 points), excluding ‘Amazonka’ which gives way to other varieties on 1-2 points. The varieties are tolerant to brown and yellow rust, powdery mildew; average tolerant to septoriosis, root rots and snow mold; they are highly sensitive to bacteriosis and fusarium of head and grain. The grain quality (vitreousness, nature weight, content of protein and gluten and its quality, falling number) is high and meets the demands of GOST for durum wheat. The technological and cooking properties of pasts are good (yellow and cream colors of pasta, strength of 800-900g, total assessment of 3.8-4.0 points). The sowings of the varieties of durum wheat both seed-growing and commercial are necessary to place apart from the sowings of winter soft wheat (at the distance of 200-500 m, not less) to avoid biological and mechanical contamination.